The indelible challenges of student attrition in Ethiopian higher education: imperatives for a closer scrutiny. (30th April 2022) - Tamrat, Wondwosen
Student attrition remains a serious challenge across the globe despite the extended attention it continues to draw. Given the meagre research available in the Global South, and particularly in Africa, this study was conducted to assess the status of student attrition in 15 Ethiopian public universities over the course of a decade (2007/08 – 2017). The study examined the scope, nature and causes of student attrition at the level of institutions, programmes and gender. The findings revealed that the attrition rate at Ethiopian public universities manifests a high level of wastage that goes against the national ambition of expanding higher education through wider participation and student success. Universities were found to be deficient in terms of tracking the progress of their students and developing a well-organised information system, hampering their potential for follow-up and early interventions. It is argued that closer scrutiny and robust responses are needed both at policy and institutional levels in order to bring about the improvements sought.